Differentiate y=(x-1)^4 with respect to x.

Using the chain rule, differentiate the "outside function" and the "inside function", and multiply the two results to get:dy/dx = 4(x-1)^3 * 1 = 4(x-1)^3

Answered by Samuel H. Maths tutor

4225 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do I maximise/minimise a given function f(x)?


Differentiate e^x^2


Differentiate the function f(x) = 2x^3 + (cos(x))^2 + e^x


integral of (tan(x))dx using the substitution u = cos(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences